PENGARUH MANAJEMEN LABA TERHADAP PROBABILITAS OPINI AUDIT: STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Anggy Marta Purnama Sari; Imam Ghozali (Diponegoro Journal of Accounting, 2016)
This study does to examine the effect of earnings management as measured by discretionary accruals as an independent variable on audit opinion probability. Audit opinion variable used divided into two categories is : (i) audit opinion for the going concern qualification (GC) and audit opinion for qualification except a going concern uncertainty (NGC). The test is done to examine the influence variables of earnings management on probability of audit opinion.This study using data types is secondary data. The study population was all manufacturing companies listed on the Indonesia Stock Exchange. The sampling method used in this research is purposive sampling with criteria of the manufacturing company that publishes an annual report and audited financial report the period of 2012-2014. This study on the test devidig the sample into two categories is  full sample of manufacturing company with the total number 291 samples and the sample companies of distressed financial with the total number is 51 samples. The analysis technique used is logistic regression analysis.The results showed  that the earnings management discretionary accruals variables significantly influence to probability of audit opinion going concern qualification (GC) the overall sample testing is full sample of manufacturing company and the sample companies of distressed financial. While the earnings management variable not significantly influence to probability of audit opinion including qualification except going concern uncertainty (NGC) the overall sample testing is full sample of manufacturing company and the sample companies of distressed financial.